NLRP3 deficiency exacerbates enterovirus infection in mice. Issue 1 (6th August 2018) - Wang, Chen; Fung, Gabriel; Deng, Haoyu; Jagdeo, Julienne; Mohamud, Yasir; Xue, Yuan Chao; Jan, Eric; Hirota, Jeremy A.; Luo, Honglin
ABSTRACT: The role for the NOD‐like receptor (NLR) P3 inflammasome in enterovirus infection remains controversial. Available data suggest that the NLRP3 inflammasome is protective against enterovirus A71 but detrimental to the host during coxsackievirus B3 (CVB3) infection. CVB3 is a common etiologic agent associated with myocarditis and pancreatitis. Previous findings on the role of NLRP3 in CVB3 were based primarily on indirect evidence. Here, we utilized NLRP3 knockout mice as well as immune and cardiac cells to investigate the direct interplay between CVB3 infection and NLRP3 activation. We demonstrated that NLRP3 knockout mice exhibited more severe disease phenotype after CVB3 infection (significantly higher virus titers), increased myocardial, and pancreatic damage, as well as markedly impaired cardiac function compared to nontransgenic control mice. We further showed that NLRP3 activity was enhanced during early stage of CVB3 infection, as evidenced by increased gene expression and/or secretion of IL‐1β and caspase‐1. Finally, we demonstrated that CVB3 inactivates the NLRP3 inflammasome by degrading NLRP3 and its upstream serine/threonine‐protein kinase receptor‐interacting protein 1/3 via the proteolytic activity of virus‐encoded proteinases. Taken together, our results reveal the functional significance of NLRP3 in host antiviral immunity against CVB3 infection and the mechanisms by which CVB3 has evolved to counteract the host defense response.—Wang, C., Fung, G., Deng, H., Jagdeo, J., Mohamud, Y., Xue, Y. C., Jan, E., Hirota, J. A., Luo, H. NLRP3 deficiency exacerbates enterovirus infection in mice. FASEB J. 33, 942–952 (2019). www.fasebj.org